FEATURES OF TOPOGRAPHIC ANATOMICAL AND MORPHOLOGICAL CHANGES OF TMJ ELEMENTS IN PATIENTS WITH UNILATERAL AND BILATERAL DISPOSITION OF ARTICULAR DISK ACCORDING TO MRI SCAN - Yu. S. Lunkova; Yu. V. Stupina; V. M. Novikov (Ukrainian Medical Stomatological Academy, 2016)
Temporomandibular joint (TMJ) disorders are found in 37-67% of dental patients and take a leading position among maxillofacial diseases. TMJ disorders are more common in woman than in man (ratio is 8,4 :1 respectively). Hvatova V.A. (1989) added such new functional disorders into the classification as dislocation of the mandibular condyle and articular disk, subluxation of the articular disk, articular disc disposition with reduction, articular disc prolapse. The aim of our study was determination and unification of structural damages and topographical changes in case of articular disc disposition by results of MRI diagnostic. MRI was used for determination of functional and morphological changes in TMJ. The investigation was conducted using apparatus «Siemens Magneton Avanto 1,5Т» (Germany) in TMJ Osag FSE T2 (oblique sagittal cut) positioning with closed and opened mouth. The results of the examination of articular disks position and form in the first group included 19 patients with unilateral articular disc disposition. Disk position was central on the right side with a closed mouth in 31,6% of cases, disk position remained central with opened mouth in 84,2% of cases. Disk position was anterior on the right side with a closed mouth in 68,4% of cases, 52,6% of which were completely anterior, 10,5% - anterior by 2/3, 5,3% - anterior by 1/2, anterior position by 1/3 was not detected. Disk position was anterior on the right side with an opened mouth in 15,8% of cases. Anterior, anterior by 1/3, and anterior by 1/2 positions were not detected. Disk position was central on the right side with a closed mouth in 57,9% of cases, disk position remained central with opened mouth in 78,9% of cases. Disk position was anterior on the left side with a closed mouth in 42,1% of cases, 5,3% of which were completely anterior, 31,6% - anterior by 2/3, 5,3% - anterior by 1/3, anterior position by 1/2 was not detected. Disk position was anterior on the left side with an opened mouth in 21,1% of cases, 15,8% of which was anterior by 2/3, 5,3% - anterior by 1/2, completely anterior position and anterior position by 1/3 were not detected. There were no anatomical changes in the right articular disks in 68,4%, disks were thinned in 15,8% of cases, degenerative changes with thinning were detected in 10,5%. Degenerative changes alone were detected in 5,3%. There were no anatomical changes in the left articular disks in 78,9%, degenerative changes were detected in 21,1%. Thinning and degenerative changes with thinning were not detected. Results of the examination of articular disks position and form in the second group included 29 patients with bilateral articular disc disposition. Disk position was central on the right side with a closed mouth in 3,4% of cases, disk position was central with opened mouth in 96,5% of cases. Disk position was anterior on the right side with a closed mouth in 96,5% of cases, 37,9% of which were completely anterior, 55,2% - anterior by 2/3, 3,4% - anterior by ½, anterior position by 1/3 was not detected. Disk position was completely anterior on the right side with an opened mouth in 3,4% of cases. Anterior by 2/3, anterior by 1/3, anterior by 1/2 positions, and completely anterior position with lateral dislocation were not detected. Disk position was central on the left side with a closed mouth in 3,4% of cases, disk position remained central with opened mouth in 93,1% of cases Disk position was anterior on the left side with a closed mouth in 96,5% of cases, 24,1% of which were completely anterior, 68,9% - anterior by 2/3, 3,4% - anterior by 1/2, anterior position by 1/3 and completely anterior position with lateral dislocation were not detected. Disk position was anterior on the left side with an opened mouth in 6,9% of cases, 3,4% were completely anterior with lateral dislocation, anterior by 2/3, anterior by 1/2, and anterior position by 1/3 were not detected. Investigation of form changes in the articular disks in patients of the second group. There were no anatomical changes in the right articular disks in 79,3%. Degenerative changes alone were detected in 20,7%. There were no patients with thinned disks or with degenerative changes with thinning. There were no anatomical changes in the left articular disks in 82,8%. Degenerative changes alone were detected in 17,2%. There were no patients with thinned disks or with degenerative changes with thinning. Results of the examination of articular disks position and form in the control group included 25 patients: disk position was central with closed mouth and did not change with opened mouth in 100% of cases. A form of articular disk did not change too. Conclusion Investigation of topographic-anatomical changes in articular disks allows planning of prosthetic treatment within the complex treatment of TMJ pathology.